(untitled) (LIS TODAY, 2024)
The main aim of this research paper is to examine and analyze the perception of user towards the use of smartphone’s in retrieving information with special reference to the University of Jammu. Smartphones are bringing the web to our door steps thus enabling the retrieval of required information from anywhere at any time. The study included total 145 participants. Google forms were distributed online to gather the viewpoint of the participants. The data was analyzed via MS-Excel. The study revealed that majority of the participants were females i.e. 73.1% and rest were male i.e. 26.9%. Further, the study revealed that majority of the participants i.e. 136 owned android phones in comparison to the others. Also, according to the results majority of the students use the smartphones with the purpose of retrieving information/ knowledge. In comparison to the use of smartphone with traditional documents majority of the participants claimed that although being more expensive, yet it is more informative and time-saving. Despite of these advantages majority of the participants i.e. 73.1% students claimed that smartphones cannot replace libraries.